Pneumonia after Major Cancer Surgery: Temporal Trends and Patterns of Care. (31st May 2016) - Trinh, Vincent Q.; Ravi, Praful; Abd-El-Barr, Abd-El-Rahman M.; Jhaveri, Jay K.; Gervais, Mai-Kim; Meyer, Christian P.; Hanske, Julian; Sammon, Jesse D.; Trinh, Quoc-Dien
Abstract : Rationale. Pneumonia is a leading cause of postoperative complication. Objective. To examine trends, factors, and mortality of postoperative pneumonia following major cancer surgery (MCS). Methods. From 1999 to 2009, patients undergoing major forms of MCS were identified using the Nationwide Inpatient Sample (NIS), a Healthcare Cost and Utilization Project (HCUP) subset, resulting in weighted 2, 508, 916 patients. Measurements. Determinants were examined using logistic regression analysis adjusted for clustering using generalized estimating equations. Results. From 1999 to 2009, 87, 867 patients experienced pneumonia following MCS and prevalence increased by 29.7%. The estimated annual percent change (EAPC) of mortality after MCS was −2.4% (95% CI: −2.9 to −2.0, P < 0.001 ); the EAPC of mortality associated with pneumonia after MCS was −2.2% (95% CI: −3.6 to 0.9, P = 0.01 ). Characteristics associated with higher odds of pneumonia included older age, male, comorbidities, nonprivate insurance, lower income, hospital volume, urban, Northeast region, and nonteaching status. Pneumonia conferred a 6.3-fold higher odd of mortality. Conclusions. Increasing prevalence of pneumonia after MCS, associated with stable mortality rates, may result from either increased diagnosis or more stringent coding. We identified characteristics associated with pneumonia after MCS which could help identify at-risk patients in order to reduce pneumonia after MCS, as it greatly increases the odds of mortality.